2016
DOI: 10.1111/cogs.12353
|View full text |Cite
|
Sign up to set email alerts
|

A Bootstrapping Model of Frequency and Context Effects in Word Learning

Abstract: Prior research has shown that people can learn many nouns (i.e., word-object mappings) from a short series of ambiguous situations containing multiple words and objects. For successful cross-situational learning, people must approximately track which words and referents co-occur most frequently. This study investigates the effects of allowing some word-referent pairs to appear more frequently than others, as is true in real-world learning environments. Surprisingly, high-frequency pairs are not always learned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 33 publications
(68 reference statements)
2
46
0
Order By: Relevance
“…Considerable evidence shows that adults and a whole variety of computational models are very good at cross-situational word-referent learning even in contexts of high uncertainty (e.g. [7,9,[19][20][21][22]). Several studies have also shown that 1-yearold infants can aggregate word-referent co-occurrence data in simple laboratory experiments with minimal visual clutter and short temporal lags between repeated naming events (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable evidence shows that adults and a whole variety of computational models are very good at cross-situational word-referent learning even in contexts of high uncertainty (e.g. [7,9,[19][20][21][22]). Several studies have also shown that 1-yearold infants can aggregate word-referent co-occurrence data in simple laboratory experiments with minimal visual clutter and short temporal lags between repeated naming events (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…To understand how learners determine word-referent mappings, researchers have sought to identify the information used to resolve referential ambiguity, revealing that learners are able to track co-occurring words and referents across moments in time. This behavior is often termed cross-situational word learning (XSWL) or statistical word learning (Benitez, Yurovsky, & Smith, 2016;Blythe, Smith, & Smith, 2016;Fitneva & Christiansen, 2011;Kachergis, Yu, & Shiffrin, 2016;Vlach & DeBrock, 2017;Vlach & Sandhofer, 2014;Yurovsky & Frank, 2015). In a typical XSWL task, participants are presented with a series of ambiguous learning trials that consist of several words and several objects within a single trial.…”
Section: Introductionmentioning
confidence: 99%
“…One possible pathway that contextual information may influence learning is through memory processes (e.g., Kachergis, Yu, & Shiffrin, in press). Some studies show that it is easier to recall lists of words from the same semantic category than lists of unrelated words (e.g., Poirier & Saint-Aubin, 1995).…”
Section: Introductionmentioning
confidence: 99%